Development and evaluation of a mobile learning application to introduce cognitive science - Chong, Jia Lu. (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study focuses on the development and implementation of an Android-based learning mobile application to introduce Cognitive Sciences. This mobile application was built by using Unity 5 and the evaluation of the development of this application was determined using a Questionnaire for User Interaction Satisfaction (QUIS) involving 30 participants. Results from the evaluation session reveal that need to be improved and recommendations for improvement are included. The internal strengths, internal weakness, external opportunities and external threats of this mobile application are outlined in SWOT analysis framework.